PENGARUH POSITIF EMOTION, TRUST, PERCEIVED EASE OF USE TERHADAP INTENTION TO USE PADA E-COMMERCE DI INDONESIA - Sa’adah, Naylatus; Setiobudi, Auditia; Vidyanata, Deandra (Parsimonia - Jurnal Ekonomi dan Bisnis, 2023)
This study was conducted to examine the effect of Positive Emotion, Trust, Perceived Ease of Use at Shopee in Java, which can affect Intention to Use. The theory used is technology acceptance model (TAM). This theory was chosen as the basis for this research because it is considered important to consider the company's priorities in increasing the use of Shopee. This study uses a quantitative non-probability sampling method. In the data collection process, there were 150 respondents with the characteristics of Generation Z who live in Java and have used Shopee with an expenditure of Rp. 500,000-Rp. 200.000. This study find indicate that there is a significant relationship between positive emotion and trust on intention to use. However, in this study, it was also found that there were variables that had no effect, namely perceived ease of use, which had no significant effect on intention to use. From these findings, it can be said that further research is needed on the phenomenon of perceived ease of use on the intention to use Shopee in Java.